แนวทางของรูปแบบความมั่นคงปลอดภัยสำหรับจัดจ้างการบริการภายนอกโดยอยู่นอกที่ทำการของผู้ว่าจ้าง - พลสินธ์ มูลสิงห์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Presently, companies cannot deny that IT outsourcing for their customers is the key growth driver. Hence, data security will become the main issue to focus on. In fact, Information technology management is a must. Therefore, IT outsourcing have to install hardware and software and maintain server in customers premise. This increases risk especially in data confidential firms such as banks or financial firms. Moreover, outsourcing usually has high cost and will cost more if there are many outsources due to redundant and duplicate resource. As a result, any IT outsourcing firm should have a proper framework for employees of customers and their customers by setting up server and operating system external to customer premise which is safe, efficient, and controllable. The purposes of this research is to provide about a security guideline for off-premise service outsourcing of IT service.